Effect of the application of structured hypocaloric diets on the reduction of metabolic syndrome risk factors - Díaz Tarazona , Amelia Madeleine (2021)
Objective. To measure the variation in the indicators of metabolic syndrome and body weight as risk factors of COVID-19, with the application of structured low-calorie diets in workers at Universidad de Huánuco. Methods. Quantitative approach, application scope, quasi-experimental design with a single study group and two measurements, to measure the change in the values of the risk factors of metabolic syndrome. Population: With a population of about 500 workers at Universidad de Huánuco, between 20 and 60 years, the sample was composed of 29 workers with overweight and metabolic syndrome. Results. The application of the  Wilcoxon statistical test to compare the middle range of two related samples resulted in signifcant changes in the number of risk factors for metabolic syndrome, having a p-value of 0.000, this being less than the signifcance value of 0.05; which allows us to reject the null hypothesis in favor of the alternative hypothesis: the application of structured low-calorie diets reduces metabolic syndrome and body weight as risk factors for COVID-20 in workers at Universidad de Huánuco. Conclusions. The application of  structured low-calorie diets at lunchtime reduces metabolic syndrome, body weight and, therefore, body mass index, abdominal perimeter, glucose, triglycerides and hypertension, thus decreasing the risk factors of complication and death in case of COVID-19 infection in workers at Universidad de Huánuco